2020
DOI: 10.1371/journal.pmed.1003190
|View full text |Cite
|
Sign up to set email alerts
|

Universal third-trimester ultrasonic screening using fetal macrosomia in the prediction of adverse perinatal outcome: A systematic review and meta-analysis of diagnostic test accuracy

Abstract: Background The effectiveness of screening for macrosomia is not well established. One of the critical elements of an effective screening program is the diagnostic accuracy of a test at predicting the condition. The objective of this study is to investigate the diagnostic effectiveness of universal ultrasonic fetal biometry in predicting the delivery of a macrosomic infant, shoulder dystocia, and associated neonatal morbidity in low-and mixed-risk populations. Methods and findings We conducted a predefined lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 56 publications
0
27
1
1
Order By: Relevance
“…In a meta-analysis of 41 studies, including 112,034 patients that had third-trimester ultrasounds for the prediction of macrosomia, the EFW did not have a clinically significant effect at predicting shoulder dystocia. Most studies reported sensitivities below 30%, and only one small study reported a sensitivity of >50% [ 180 ]. Untreated diabetes in pregnancy was associated with an increased rate of shoulder dystocia (risk ratio, 1.25 compared to controls).…”
Section: The Effects Of Diabetes In Pregnancy On the Newborn Infanmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis of 41 studies, including 112,034 patients that had third-trimester ultrasounds for the prediction of macrosomia, the EFW did not have a clinically significant effect at predicting shoulder dystocia. Most studies reported sensitivities below 30%, and only one small study reported a sensitivity of >50% [ 180 ]. Untreated diabetes in pregnancy was associated with an increased rate of shoulder dystocia (risk ratio, 1.25 compared to controls).…”
Section: The Effects Of Diabetes In Pregnancy On the Newborn Infanmentioning
confidence: 99%
“…Antoniou et al found 8.2% premature births among 576 diabetic pregnancies associated with HbA1c ≥ 5.5% at the end of pregnancy [ 187 ]. Prematurity was more common among women with type 1 and 2 PGDM without pre-pregnancy care (17.7% of 265) compared to women with pre-pregnancy care (11.4% of 149), p = 0.09 [ 180 ]. Kawakita evaluated 222,978 singleton pregnancies, of them, 11,327 (5%) had GDM and 3296 (1.5%) PGDM and found prematurity rate of 16.3% and 32.3% among GDM and PGDM, respectively, compared to controls (10.9%) [ 188 ].…”
Section: The Effects Of Diabetes In Pregnancy On the Newborn Infanmentioning
confidence: 99%
“…Fetal ultrasonography is commonly used to evaluate fetal growth in clinical practice, and most studies use conventional biometry (estimated fetal weight). Estimated fetal weight has been reported to be a useful predictor of fetal macrosomia (18), or fetal growth restriction with decreased percent body fat (19). However, the estimated fetal weight can fluctuate by approximately 15% compared to the actual weight and has poor accuracy, especially for fetuses with growth restriction or macrosomic infants (20).…”
Section: Ultrasound-based Measures Of Fetal Weightmentioning
confidence: 99%
“…In most settings, the rationale for third‐trimester ultrasound – whether universal or selective – is aimed at identifying fetuses at risk of adverse perinatal outcome due to growth restriction, 3 abnormal Doppler studies, 4 macrosomia 5 or non‐cephalic presentation 6…”
mentioning
confidence: 99%